Accelerating financial inclusion in South East Asia with digital finance. - Wyman, Oliver (Asian Development Bank, 2017)
This study focuses on four Southeast Asian markets Indonesia, the Philippines, Cambodia, and Myanmar. It is informed by more than 80 stakeholder interviews across the four markets, extensive secondary research, and economic analysis and seeks to better understand and quantify the nature of the impact of digital finance on accelerating financial inclusion.The research focuses on financial exclusion in three segments: base of pyramid; women; and micro, small, and medium enterprises (MSMEs). It is estimated that addressing this opportunity could increase gross domestic product (GDP) by between 9% and 14%, even in relatively large economies such as Indonesia and the Philippines. The potential boost to GDP is as high as 32% in Cambodia. Making the most of this opportunity could also help influence the future shape of the financial services industry, particularly in smaller markets such as Cambodia and Myanmar, where only a small percentage of the current needs for financial services are met by formal providers.While digital finance alone cannot entirely close the gaps in financial inclusion, the estimated cumulative effect of digitally driven acceleration in financial inclusion could boost GDP by 2% to 3% in markets like Indonesia and the Philippines, and 6% in Cambodia. For the population earning less than 2 dollar a day, that would translate to a 10% increase in income in Indonesia and the Philippines, and an increase of around 30% in Cambodia.